International Partnership in Russia : Conclusions from the Oil and Gas Industry - Henderson, James; Ferguson, Alastair; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
International Partnership in Russia provides a unique insight into the joint ventures formed by international oil companies in Russia during the post-Soviet era. It outlines the highs and lows in their fortunes and analyses the reasons for their successes and failures.
Keywords: Science; Science; Science, general